PENGARUH BAURAN PEMASARAN RITEL DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN PADA GIANT SUPERMARKET SCP (SAMARINDA CENTRAL PLAZA) SAMARINDA - AGNES AYU SASMITA SA; SUAHRNO -; RAHMAWATI - (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
This study aimed to determine the effect of Merchandising , basic principles, service , customer satisfaction to customer loyalty at Giant Supermarket SCP ( Samarinda Central Plaza ) Samarinda , using multiple regression analysis. Results showed variable Merchandising variables , basic principles, service, customer satisfaction together positive and significant impact on customer loyalty . The R value of 0.482 means that there is a relationship which was of variable Merchandising , basic principles, service, customer satisfaction to customer loyalty . The coefficient of determination ( R2 ) of 23.20 per cent it shows the proportion of variable contribution Merchandising , basic principles, service , customer satisfaction to fluctuations in customer loyalty.Keyword: Merchandising , basic principles, service , customer satisfaction and customer loyalty